Exploring faculty retention at community colleges: Insights from demographic and institutional factors - Sivells, Melenese; Bista, Krishna; Parsons, Michael (American Journal of STEM Education, 2025)
This quantitative cross-sectional survey study investigates the relationships between demographic characteristics, campus climate perceptions, and retention plans of faculty at community colleges in the North Atlantic Region of the United States. Data were collected from 335 faculty members across three institutions using the "Faculty Retention Questionnaire". Findings indicate that age, ethnicity, relationships with students, and personal satisfaction significantly influence faculty retention plans. Younger faculty reported higher satisfaction levels across campus climate, role clarity, and personal satisfaction, while faculty of color scored lower in campus climate satisfaction and role clarity compared to their White counterparts. Key factors influencing retention include salary, job security, and career advancement opportunities, while geographical location and visa sponsorship had minimal impact.